All‐Inorganic‐State Fabric Lead‐Free Piezoelectric Nanogenerators. Issue 20 (23rd February 2022) - Kim, Hyunseung; Jeong, Chang Kyu
Abstract : Highly efficient and economical wearable piezoelectric energy harvesters are required to achieve future human‐integrated self‐powered electronics with stability. Herein, an all‐inorganic‐state fabric piezoelectric nanogenerator (FPNG) is developed for high‐performance energy harvesting using a spray‐coated lead‐free piezoceramic layer on a glass fabric. 0.5(Ba0.7 Ca0.3 )TiO3 –0.5Ba(Zr0.2 Ti0.8 )O3 (BCTZ) sol–gel solution is deposited by spray coating, which is very facile and cost‐effective processing for the textile industry. It is well‐annealed and crystallized on the glass fabric endurable in high‐temperature processes. The BCTZ‐coated glass fabric is also treated by spraying silver nanowire (AgNW) solution onto both sides of the fabric to form robust electrodes. The all‐inorganic‐state FPNG can generate electrical output about the voltage of ≈3 V and the current of ≈110 nA which are high‐performance energy harvesting signals compared to previously reported fabric‐type energy harvesters. This high‐output energy harvesting results from the effective piezoelectricity of inorganic piezoceramics on the robust glass fabric. This work would open ways for future wearable self‐powered electronics integrated in general textile. Abstract : All‐inorganic‐state fabric piezoelectric nanogenerator is demonstrated by spray‐coating methods for lead‐free piezoelectric ceramic films and silver nanowire (AgNW) network electrodes on a glass fabric. Previous fabric‐approached studies are reported with disadvantages such as poor piezoelectric polymers/composites, complex processes, or incompatible device structures. In contrast, the device shows mechanical flexibility, good energy harvesting performance, facile fabrication, and high durability.